Economic impacts of multilateral emission reduction policies: Simulations with WorldScan - J. C. Bollen; Arjen M. Gielen (Fondazione Eni Enrico Mattei (FEEM), 1998)
Using an applied general equilibrium model, we explore the impacts of uniform reduction targets, a uniform carbon tax, and permit trading in the Annex 1 countries for the period 2000-2020. Next, we assess the impacts of enlarging the A-1 coalition to the globe, and allow for global permit trading. The impacts suggest among others that more research is necessary on how to change the size of the coalition.
Keywords: 330; Umweltabkommen; Immissionsschutz; Ökosteuer; Treibhausgas-Emissionen; Emissionshandel; Allgemeines Gleichgewicht; Theorie; Welt